1993
DOI: 10.7326/0003-4819-119-5-199309010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation after Successful Treatment of Small-Cell Lung Cancer Is Associated with Fewer Smoking-related Second Primary Cancers

Abstract: Patients with small-cell lung cancer who survive cancer-free for more than 2 years have a significantly increased risk for development of a second primary smoking-related cancer. Cigarette smoking cessation after successful therapy is associated with a decrease in risk for a second smoking-related primary cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
127
1
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(134 citation statements)
references
References 0 publications
1
127
1
5
Order By: Relevance
“…Studies have suggested that exposure to nicotine can enhance the metastatic potential of NSCLC (10,47). Experiments were conducted to assess how depletion of ID1 affected the invasive property of A549 and H1650 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have suggested that exposure to nicotine can enhance the metastatic potential of NSCLC (10,47). Experiments were conducted to assess how depletion of ID1 affected the invasive property of A549 and H1650 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Smoking cessation can improve survival, treatment efficacy, and improve overall quality of life [2][3][4] . Approximately half of all smokers have quit prior to their diagnosis 5 .…”
mentioning
confidence: 99%
“…Even among individuals diagnosed with lung carcinoma, smoking cessation reduces the risk of development of a second primary tumor. 2,3 Research has also demonstrated that individuals who continue to smoke after a cancer diagnosis report lower quality of life compared with individuals who stop smoking. 4 However, it has been estimated that 30 -60% of smokers will continue to smoke after being diagnosed with cancer.…”
mentioning
confidence: 99%